KARAKTERISTIK PROSES HIDROKONVERSI KATALITIK DENGAN BAHAN BAKU BITUMEN - Yusnitati, Yusnitati; Hanif, Muhammad; Adiarso, Adiarso (Jurnal Energi dan Lingkungan (Enerlink), 2010)
The effects of bitumen types in a hydro-conversion catalytic process to producesyntethic liquid fuels was investigated. Three samples of natural solid bitumenobtained from three different sampling points in Riau Province are used in thisstudy. Preliminary technical feasibility of the natural solid bitumen as a feedstockof synthetic fuel oil using this process is also investigated. Experimental runs arecarried out using a 1 liter stirred batch autoclave reactor under the standardconditions: reaction temperature of 450oC, initial hydrogen pressure of 12 MPafor 1 hour and atomic ratio of sulfur to iron at 2.0. This process condition issimilar to direct coal liquefaction process using heavy oil solvent produced fromBench Scale Unit (BSU) 100 kg/hour input in Takasago, Japan. The resultsindicate that the oil yield increases with the decrease of liquid bottom yield. TotalCO+CO2 and hydrocarbon gases products are almost equal at all bitumensamples. Due to their high ash content, the oil yield (LO, MO and HO) of bitumensamples relatively lower than the oil yield of coal liquefaction process. It was alsofound that O/C and H/C atomic ratio in bitumen samples vary significantly withtheir sampling point, but the H/C ratio of bitumen relatively higher than typicalcoal. The higher of H/C ratio, the easier of bitumen to be converted to syntheticfuel oil and leading to the more efficiently use of gaseous hydrogen. Inconclusion, the natural solid bitumen has a possibility as a feedstock of syntheticfuel oil, if it is fed to the process in the form of a dried-ash-free-bitumen (hyperbitumen).Kata kunci: bitumen, hidrokonversi katalitik, BBM sintetis